A hierarchical framework for open access to education and learning. (1st January 2014) - Sampson, Demetrios G.; Zervas, Panagiotis
During the last years, several Open Educational Resources (OERs) initiatives around the world have been developed, which aim to create and share digital educational resources that are openly licensed and available online for everyone to use. These initiatives have contributed in building and sustaining web-based educational communities and communities of best teaching practices. According to the various existing definitions, the term OER is subject to different interpretations, such as open educational content, open courseware and open source software. This means that OERs are not limited only to open educational content and they can be of different granularity and different formats. In this paper, we propose a hierarchical open access framework that considers different hierarchical elements for supporting the main stages of a typical e-learning chain and we present a set of tools that support this framework. In our proposed framework, OERs are treated in a modular manner considering the different levels of granularity, the relationships between the different levels and the different tools and services needed to handle the particularities of each granularity level. This aims to support the main stages of a typical e-learning chain, namely, creation, publication, discovery, acquisition, access, use, re-use and delivery of OERs.